Thickness of Neurocranium Bones of Deceased Adults: A Cross-Sectional Study - Bhushal, Kumar; Adhikari, Bidur; Bhandari, Rosha; Dhungel, Deepesh; Gautam, Jyoti; Gautam, Subina; Phuyal, Navindra; Shrestha, Anusuya (Journal of Institute of Medicine Nepal, 2025)
Introduction Thickness of neurocranium is not regular throughout the skull and cranial vault thickness is often observed to be higher in females when compared to males. This study aimed to measure the thickness of neurocranium of deceased adults and compare it across sex, age and laterality. MethodsThis was a cross-sectional study in which 72 deceased adults were enrolled, that presented in the mortuary of the Department of Forensic Medicine and Department of Anatomy of Maharajgunj Medical Campus. Measurements were taken after ethical approval from Institutional Review Committee of Institute of Medicine and after obtaining written informed consent from the relatives of the deceased. Measurements were taken in 9 points total, using an iGaging 8” Digital Outside Caliper. Independent sample t-test was done to compare the thickness between sexes and one-way ANOVA was done to compare the thickness between the bones.ResultsThe mean thickness of frontal, parietal, temporal, occipital bones, and pterion were 5.38(±0.91), 4.67(±0.59), 1.52(±0.50), 6.53(±1.28) and 2.55(±0.74) mm respectively. Thickest point was Occipital Point B with mean thickness of 7.39(±1.70) mm in females and 8.47(±1.46) mm in males and the thinnest point was found to be the squamous part of temporal bone with the mean thickness of 1.48(±0.69) mm in the right 1.65(±0.69) mm in the left cranium of females and 1.43(±0.41) mm in the right and 1.56(±0.40) mm in the left cranium of the males.ConclusionOccipital bone was the thickest bone in the neurocranium and the thickness increased from anterior to posterior side. This study will be helpful for surgeons in bone grafting and selecting screws and will also be resourceful to anatomists and anthropologists.